2022
DOI: 10.1182/bloodadvances.2021004618
|View full text |Cite
|
Sign up to set email alerts
|

A germinal center–associated microenvironmental signature reflects malignant phenotype and outcome of DLBCL

Abstract: Diffuse large B-cell lymphoma (DLBCL) is the most common B-cell malignancy with varying prognosis after the gold standard rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP). Several prognostic models have been established by focusing primarily on characteristics of lymphoma cells themselves, including cell-of-origin, genomic alterations, and gene/protein expressions. However, the prognostic impact of the lymphoma microenvironment and its association with characteristics of lymphoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 56 publications
(78 reference statements)
0
8
0
Order By: Relevance
“…Interestingly, this prognostic model was inversely correlated with genomic alterations, gene expression, and phenotypes such as doubleexpressor lymphoma, which are known to be associated with a poor prognosis. 85 Collectively, these data suggest that the LME signature reflects the multifaceted signatures of tumor cells themselves that explain the malignant activity of DLBCL. This opens up the possibility of developing a simple prognostic tool that reflects information that would be known through various omics tests such as IHC, FISH, genomic mutation, and gene expression profiling.…”
Section: The Lymphoma Microenvironment Based On Integrative Analysismentioning
confidence: 88%
See 3 more Smart Citations
“…Interestingly, this prognostic model was inversely correlated with genomic alterations, gene expression, and phenotypes such as doubleexpressor lymphoma, which are known to be associated with a poor prognosis. 85 Collectively, these data suggest that the LME signature reflects the multifaceted signatures of tumor cells themselves that explain the malignant activity of DLBCL. This opens up the possibility of developing a simple prognostic tool that reflects information that would be known through various omics tests such as IHC, FISH, genomic mutation, and gene expression profiling.…”
Section: The Lymphoma Microenvironment Based On Integrative Analysismentioning
confidence: 88%
“…83,84 Recently, our group exploited the nCounter system to semi-comprehensively screen genes related to tumor cells and microenvironment-related genes, in combination with whole transcriptome screening by RNA-seq, to determine the prognostic genes in DLBCL. 85 As a result, many microenvironment-related genes, especially those of follicular T cells (Tf), dendritic cells/macrophages (DC/Mφ), and stromal cell lineages, were extracted as prognostic genes rather than tumor cell-related genes. A simple prognostic score, which we called the DLBCL Microenvironment Signature (DMS) score, was generated using the most powerful prognostic genes among each LME component: ICOS (Tf marker), CD11c/ITGAX (DC/Mφ marker), and FGFR1 (stromal marker).…”
Section: The Lymphoma Microenvironment Based On Integrative Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the comprehensive investigation of non-immune cell components in the TME is still lacking. Previous research on stroma in DLBCL has predominantly indicated that a higher quantity of extracellular matrix is associated with a more favorable prognosis, while increased vascular density is associated with poorer prognosis [9]. Furthermore, higher stromal scores have been associated with an improved prognosis in DLBCL patients [10].…”
Section: Introductionmentioning
confidence: 99%